The Welfare State and its Effect on Municipal Government in Japan: A Case Study - Yasuo, T. (Cambridge University Press, 1998)
Since the end of World War II, the ever-increasing role of government in advanced democratic nations has resulted in a massive organizational growth in the public sector. The impact of the welfare state provides an explanation for changes in traditional patterns of central-local government relations. The era of the welfare state has witnessed the rapid emergence of an intermeshed system of making and implementing policies, which necessitates integration between central and local government. Japan has also dealt with the dramatically increased public sector, but has one so in a setting of institutional centralization. How has central authority sought to find ways to managing the continuous expansion of state activities? How have local authorities responded to central government's initiative in integrating state administration? This article will conduct a case study in order to answer these questions.